South Asian women’s lived experiences of health care after disclosure of family violence: a qualitative meta-synthesis review - Surriya Baloch; Elizabeth McLindon; Mohajer Hameed; Kelsey Hegarty (BMC Public Health)
Abstract Introduction Given the high prevalence of family violence (FV) amongst South Asian women, the experiences and expectations of addressing FV within healthcare, is of policy, practice and research interest. Whilst FV is shaped and influenced by various interconnected sociodemographic and cultural factors, it can be addressed in healthcare settings through identification and response. Objective To explore South Asian women's lived experiences and expectations about identifying and responding to FV within healthcare. Methods This review utilised a systematic methodology; nine databases were searched up to June 2024. A total of 8,217 records were screened by two reviewers independently based on a priori inclusion and exclusion criteria. A thematic analytical approach guided the integration of findings from 14 qualitative studies. Results Thematic synthesis of the articles generated three themes (1) I was afraid to share, (2) They just walk away, (3) Understand and listen to my pain. These themes represented the perspectives, feelings, and expectations of both local and migrant South Asian women survivor participants. Cultural factors and social obstacles may prevent South Asian women from seeking and using appropriate support services. Additional barriers may include healthcare providers’ reluctance to address FV with South Asian women because of a lack of cultural knowledge and/or appropriate methods to address FV. South Asian women participants reflected that they want healthcare providers to understand them, acknowledge their discomfort, and provide culturally appropriate strategies and solutions. Conclusion It is highly recommended that policymakers and health-care providers continue to be mindful of the social and cultural challenges faced by South Asian women who experience FV.